Penerapan Metode Membaca SQ4R untuk Meningkatkan Kemampuan Siswa dalam Menentukan Unsur-Unsur Karya Fiksi Cerpen di Kelas VIII Sekolah Menengah Pertama - Silvia Niat Sari Nazara; Noveri Amal Jaya Harefa; Imansudi Zega; Arozatulo Bawamenewi (Pusat riset dan Inovasi Nasional, 2025)
This study aims to improve the ability of eighth grade students of SMP Negeri 2 Sogaeadu in identifying short story elements through the application of the SQ4R method. The background of this study is the low interest of students in reading literary works and their lack of understanding of effective reading strategies. The study used a Classroom Action Research (CAR) design which was carried out in two cycles, each including the planning, implementation, observation, and reflection stages. The results showed a significant increase in student learning outcomes, from an average of 59.2% in cycle I to 82.4% in cycle II. The percentage of student involvement also increased from 42%-52% (cycle I) to 71%-90% (cycle II), while observations of researcher performance increased from 56%-75% (cycle I) to 87.5%-100% (cycle II). These findings prove that the SQ4R reading method is effective in improving students' ability to identify short story elements through systematic and easy-to-apply steps.